Effect of mechanical recycling and virgin PBR addition on the properties of ABS recovered from WEEE: A multi-technique characterization - Lesiak, Anna; Vincent, Luc; Schollaert, Joost; Safou, Lamiae; Orange, Francois; Pagnotta, Sophie; Sbirrazzuoli, Nicolas; Guigo, Nathanael (Waste Management Bulletin, 2025)
•Extrusion raises T10% by ∼30 °C and improves ABS particle size homogeneity.•Virgin PBR improves matrix cohesion and induces fibrous recyclate morphology.•Multi-technique approach enables complete characterization of recycled ABS.•Findings support tuning recyclate quality by extrusion and additive strategy. With the growing use of electrical and electronic devices, the volume of waste electrical and electronic equipment (WEEE) continues to increase, posing a major environmental and recycling challenge. Acrylonitrile-butadiene-styrene (ABS) is one of the most common thermoplastics found in WEEE, its recovery is complicated by contamination, heterogeneity, and degradation. While mechanical recycling of ABS is widely practiced, the impact of specific processing steps on the chemical and physical properties of the recyclate remains insufficiently explored. This study investigates the effect of shredding and extrusion, as well as the integration of virgin polybutadiene rubber (PBR), on the morphology, chemical structure, and thermal stability of ABS-rich WEEE recyclates. A multi-analytical approach, combining Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), inductively coupled plasma optical emission spectroscopy (ICP-OES) and thermal analysis − was employed to fully characterize the materials. Our findings show that extrusion improves sample homogeneity and removes some contaminants (e.g., Ba, Cl), leading to a significant increase in thermal stability (T10% +30 °C). The addition of virgin PBR contributes to enhanced internal cohesion and a fibrous morphology. This work provides a robust methodology for distinguishing processing-related changes from compositional variability in real-world recycled plastics. The approach can support the development of advanced processing strategies for polymer waste streams.